PENGARUH KUALITAS PRODUK, INOVASI DAN KREATIVITAS TERHADAP MINAT BELI ULANG KONSUMEN PADA PEMPEK OWEN KOTA BENGKULU - Ramadansah, Jepri (UM. Bengkulu, 2025)
The aim of this research is to determine the influence of product quality, innovation and creativity on consumer repurchase interest in Pempek Owen, Bengkulu City. Quantitative descriptive research method. In collecting data, researchers used observation methods, interview methods, documentation and questionnaires for Pempek Owen customers in Bengkulu City. The data analysis methods used were multiple linear regression, coefficient of determination and hypothesis testing. The results of this research show that: (1) Product quality has a significant effect on consumer repurchase interest with a tsig value of 0.011 with a beta coefficient value. The tsig value = 0.011 < 0.050 which means Ho is rejected and Ha is accepted. (2) Innovation has a significant effect on consumer repurchase interest with a tsig value of 0.001, tsig value = 0.001 < 0.050, which means Ho is rejected and Ha is accepted. (3) Creativity has a significant effect on consumer repurchase interest with a tsig value of 0.000. tsig value = 0.000 < 0.050 which means Ho is rejected and Ha is accepted (4) The variables Product Quality (X¬1), Innovation (X2) and Creativity (X3) have a significant effect on consumer repurchase interest (Y) with a valuetsig 0.000<0.05Keywords: Product Quality, Innovation, Creativity, Repurchase Intention